DEVELOPMENT OF FLASHCARD LEARNING MEDIA USING THE CANVA APPLICATION ON SPACIOUS FIGURES IN THE MATHEMATICS SUBJECT FOR GRADE IV ELEMENTARY SCHOOL - Aulia Vitaloka Dimalaw; Beta Rapita Silalahi (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This study aims to develop Flashcard learning media using the Canva application as a Mathematics Learning Media for Flat Building Materials for Class IV. It is expected that after using this learning media, students will find it easier to understand the material on spatial buildings so that learning objectives are achieved. ADDIE development procedure consisting of 5 stages. However, in this study, the researcher carried out the development procedure only up to stage 3, namely Development. The instrument used to collect data was a questionnaire given to several expert reviewers, namely media expert validators, material expert validators and learning expert validators. The validation score obtained from the media expert validator was 91 with the category "Very Eligible". The feasibility score from the material expert was 81.06 with the category "Very Eligible". The feasibility score from the learning expert was 83 with the category "Very Eligible". From this score, it can be said that the Development of Flashcard Learning Media Using the Canva Application on the Material on Spatial Buildings for Class IV Elementary School Mathematics is "Very Eligible" for use in the learning process.